RAMBU SOLO AND BUFFALO AT TANA TORAJA OF SOUTH SULAWESI - Saleh, Ikrar Mohammad; Sirajuddin, Sitti Nurani; Aminawar, Muhammad (Proceeding Buffalo International Conference, 2013)
Toraja traditional feast